2015
DOI: 10.1017/s095927091500026x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal and age sources of variation in parrot poaching in Bolivia

Abstract: SummaryParrot poaching and the subsequent illegal trade in the Neotropics are exacerbating the decline in parrot populations. Little is known, however, on where, when and how parrots are poached. The goals of this study were to identify the spatio-temporal patterns of parrot poaching in order to identify ways in which poaching could be reduced, using parrot data (9,013 individuals from 27 species) collected daily in a major illicit wildlife market in Santa Cruz de la Sierra, Bolivia, in 2005. Parrot data ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…On the other hand, the relative abundance in natural habitats of the Hispaniolan amazon resulted one to two orders of magnitude lower than that of two amazon species also listed by IUCN as Vulnerable, the red-spectacled amazon ( A. pretrei , ×109 times higher) and the vinaceus amazon ( A. vinacea , ×23 times higher), in the Atlantic Brazilian forests ( Tella et al, 2016b ). Even the blue-fronted amazon ( A. aestiva ) living in the inter-Andean valleys of Bolivia, where populations are suffering from strong poaching pressure for the domestic pet trade ( Pires, Herrera & Tella, 2016 ), showed a relative abundance 3.3 times higher ( Blanco et al, 2015 ) than the Hispaniolan amazon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the relative abundance in natural habitats of the Hispaniolan amazon resulted one to two orders of magnitude lower than that of two amazon species also listed by IUCN as Vulnerable, the red-spectacled amazon ( A. pretrei , ×109 times higher) and the vinaceus amazon ( A. vinacea , ×23 times higher), in the Atlantic Brazilian forests ( Tella et al, 2016b ). Even the blue-fronted amazon ( A. aestiva ) living in the inter-Andean valleys of Bolivia, where populations are suffering from strong poaching pressure for the domestic pet trade ( Pires, Herrera & Tella, 2016 ), showed a relative abundance 3.3 times higher ( Blanco et al, 2015 ) than the Hispaniolan amazon.…”
Section: Discussionmentioning
confidence: 99%
“…Parrots are long-lived species with slow reproduction rates ( Young et al, 2012 ), and thus the overharvesting of adults (through hunting and trapping) has a higher impact on population dynamics than nest poaching ( Pires, Herrera & Tella, 2016 ; Valle et al, 2018 ). Nest poaching to supply the pet trade has ancestral cultural roots in Hispaniola Island ( Wiley & Kirwan, 2013 ; White et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most parrots nest in elevated cavities in trees or cliffs that are difficult to find, reach, and monitor. Capturing parrots outside of their nests is challenging, since most species usually fly high over the canopy and avoid traps, although trapping can be successful at foraging sites (Pires et al 2016). Parrots typically have strong bills and can remove plastic bands or crush aluminium bands on their legs, leading to injuries.…”
Section: Parrot Traits Hinder Estimation Of Abundance and Population mentioning
confidence: 99%
“…On the other hand, the relative abundance in natural habitats of the Hispaniolan amazon resulted one to two orders of magnitude lower than that of two amazon species also listed by IUCN as Vulnerable, the red-spectacled amazon (Amazona pretrei, x109 times higher) and the vinaceus amazon (Amazona vinacea, x23 times higher), in the Atlantic Brazilian forests (Tella et al 2016b). Even the blue-fronted amazon (Amazona aestiva) living in the inter-Andean valleys of Bolivia, where populations are suffering from strong poaching pressure for the domestic pet trade (Pires et al 2016), showed a relative abundance 3.3 times higher than the Hispaniolan amazon.…”
Section: Large-scale Parrot Population Declinesmentioning
confidence: 98%
“…Parrots are long-lived species with slow reproduction rates (Young et al 2012), and thus the overharvesting of adults (through hunting and trapping) has a higher impact on population dynamics than nest poaching (Pires et al 2016;Valle et al 2018). Nest poaching to supply the pet trade has ancestral cultural roots in Hispaniola Island (Wiley & Kirwan 2013;White et al 2011).…”
Section: Large-scale Parrot Population Declinesmentioning
confidence: 99%